KAJIAN TINGKAT PENGETAHUAN MASYARAKAT DALAM UPAYA PELESTARIAN LINGKUNGAN HIDUP AKIBAT PENAMBANGAN BATU KAPUR DESA TAHUNAN, KECAMATAN SALE, KABUPATEN REMBANG - Wulandari, Dhesy Ayu (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2016)
Environment could be damaged or maintained in accordance with community behavior and life style. Thisstudy aims to determine community knowledge level about environmental conservation, to knowenvironmental conservation efforts due to limestone mining in Tahunan Village and to determine the extentof influence between community knowledge to their behavior of environmental conservation as a result ofmining limestone in the Tahunan Village. Population in this study were Tahunan Village community whoworked as miners, in number 758 person, with number of sample 86 people. Sampling technique usedproportional stratified random sampling. This research type was quantitative. Data were collected byquestionnaire. Data analysis technique used descriptive analysis and regression analysis simple percentage.Results showed that knowledge level of Tahunan Community was high and the conservation efforts weregood. The regression analysis showed there was effect between knowledge levels to environmental protectionefforts due to limestone mining by 54%. There are positive influence between the two variables, if high levelof miner’s knowledge, then followed by high efforts of environmental conservation.